Letters relating to the John Devoy Funeral Committee - John Devoy Funeral Committee (1929)
Two circular letters from the John Devoy Funeral Committee inviting attendance at meetings in the Mansion House, Dublin, to organise the repatriation of Devoy's body.
Keywords: Devoy, John, -- 1842-1928; Ireland -- History -- 1922-